Internet Addiction among Undergraduate Medical Students and its Association with Sensation-Seeking Traits - Sawant, Sandesh; Chand Thakuri, Amit; Gupta, Pramanand Prasad; Karki, Isha; Mahseth, Pritika; Chapagain, Manisha (Journal of Institute of Medicine Nepal, 2025)
Introduction: Easy access to the internet has raised concerns about internet addiction among medical students. This study aimed to assess the prevalence of internet addiction and its relationship with sensation-seeking traits. Methods: A cross-sectional study was conducted at National Medical College, Birgunj, Nepal, from January to June 2023. Ethical approval was obtained from the Institutional Review Committee (Ref. No: F-NMC/620/079-080). Undergraduate medical students were selected through convenience sampling. The Internet Addiction Test (IAT) and Arnett Sensation Seeking Scale were used for data collection, and data were analyzed using SPSS 21 with descriptive statistics, t-test, and Pearson correlation. Results: The study included 155 undergraduate medical students (Mean age: 21.22 ± 1.649 years). Most were fourth-year (n=58, 37.4%), followed by first-year (n=42, 27.1%), second-year (n=29, 18.7%), and third-year (n=26, 16.8%) students. Internet addiction was found in 86 students (55.5%), with 84 (54.2%) showing problematic and 2 (1.3%) severe use. High sensation-seeking traits were observed in 47 (30.3%). Weak negative correlations were found between internet addiction and sensation-seeking (r = -0.143 to -0.126, p > 0.05). Gender differences were observed in sensation-seeking (p = 0.022) and intensity (p < 0.001), but not in internet addiction or novelty (p > 0.05). Conclusion: The study found a high prevalence of internet addiction, with weak negative correlations to sensation-seeking traits, highlighting the need for awareness and interventions on healthy internet use.